Exploring diverse aspects of celiac disease - A review - Chandrakar, Akanksha (Recent Research in Science and Technology, 2024)
Celiac disease is a chronic inflammatory disorder triggered by the ingestion of gluten-containing foods in genetically susceptible individuals. This multifactorial disease has both genetic and environmental components, with gluten serving as the environmental trigger and specific genetic variations in the major histocompatibility complex region contributing to the genetic predisposition. Contrary to previous assumptions, celiac disease is not a rare disorder, with a global prevalence estimated at approximately 1%. However, it often remains under-recognized because many affected individuals do not exhibit the classic gastrointestinal symptoms associated with the condition. Instead, they may present with nonspecific manifestations of nutritional deficiencies or may be entirely asymptomatic. Celiac disease is associated with an increased incidence of autoimmune disorders, and its identification in asymptomatic or silent cases is crucial for managing associated conditions and preventing long-term complications such as lymphoma. The relationship between celiac disease and other autoimmune disorders, particularly type 1 diabetes, suggests a potential trigger role for gluten. In this article we review the development of celiac disease, including its types, pathogenesis, clinical features, and associated diseases or complications. We will also discuss available tests, treatments, and preventive approaches related to this subject.